Comparative Pharmacology of Josamycin and Erythromycin Stearate - Strausbaugh, Larry J. (1976)
Two macrolide antibiotics, josamycin and erythromycin stearate, were administered orally to healthy, adult male volunteers for a comparative study of their pharmacological properties. In comparable doses, josamycin and erythromycin produced similar plasma concentrations, with similar half-lives and elimination constants. An initial loading dose of 1.5 g of josamycin produced greater peak concentrations of antibiotic throughout a 10-day period with a regimen of every 6 h. In addition, josamycin tended to reach higher peak and trough concentrations after regimens of every 6 or 8 h were maintained for 2 days. Josamycin penetrated into saliva, sweat, and tears, and it was better tolerated in fasting subjects than was erythromycin stearate.